Limestone Microfacies Punung Formation at Bangbang River, Sumbermanjing Wetan, Malang, East Java - Winarti Winarti; Herning Wijayanti; Odhi Febriarto (Journal of Wetlands Environmental Management, 2021)
Malang and Wonosari areas are located in Southern Mountains of Java, and their rock variations are comparable. Study focuses on limestone found at Sumbermanjing Wetan, Malang, that has been identified as part of Wonosari Formation. This place is closer to Punung area as viewed from the type location. Limestone microfacies approach is used to determine whether the limestone belongs to Wonosari or Punung formations. Methods used to identify standard microfacies types and facies zone are measured stratigraphy, petrographic analysis, and microfossil analysis. Measured stratigraphy was conducted along Bangbang River, and seven limestone samples were collected for analysis. Findings showed three standard microfacies types: SMF-5 characterized by packstone or rudstone with a mudstone matrix, SMF-8 characterized by wackstone or floatstone with complete fossils, and SMF-18 characterized by grainstone or packstone with abundant foraminifera or algae. Limestone belongs to facies zone (FZ) 7 - 8, which is characterized by presence of packestone, wackestone, clay sized limestone, and benthic algae foraminifers. Limestone ages range from Middle to Upper Miocene (N12 - N16), were formed in an inner Neritic. Limestone is equivalent to Wonosari and Punung Formations, based on standard microfacies type, facies zone, and age range. When lignite intercalation are present, the limestone is equivalent to the Punung Formation.